One gene, many phenotypes: the role of KIF5A in neurodegenerative and neurodevelopmental diseases - Marta Cozzi; Barbara Tedesco; Veronica Ferrari; Marta Chierichetti; Paola Pramaggiore; Laura Cornaggia; Rocio Magdalena; Maria Brodnanova; Ali Mohamed; Carmelo Milioto; Margherita Piccolella; Mariarita Galbiati; et al. (Cell Communication and Signaling)
Abstract Kinesin family member 5 A (KIF5A) is a neuron-specific molecular motor involved in anterograde transport. KIF5A mediates a wide range of trafficking processes that are only partially shared with the other members of the KIF5 family. Since 2002, several disease-causing mutations have been found in the KIF5A gene and a link between the specific domain in the encoded protein affected by mutations and the associated phenotype has become evident. Point mutations targeting KIF5A motor and stalk domains, that are expected to impair KIF5A motility, mainly associate with spastic paraplegia type 10 (SPG10) and axonal Charcot-Marie-Tooth (CMT) disease. Oppositely, translational frameshifts causing the elongation of KIF5A tail enhance KIF5A migration towards cell periphery, induce kinesin aggregation, and are linked to amyotrophic lateral sclerosis (ALS) or neonatal intractable myoclonus (NEIMY). This review correlates KIF5A structure and roles in neuronal trafficking with its involvement in the above-mentioned neurodegenerative and neurodevelopmental conditions.